(untitled) (Fiep Bulletin - online, 2025)
Introduction: The female menstrual cycle involves hormonal variations that prepare the body for a possible pregnancy, resulting in endocrine and anatomical changes. This process is regulated by gonadotropin-releasing hormone (GnRH) from the hypothalamus, and is divided into four phases: menstrual, pre-ovulatory, ovulatory and post-ovulatory. Different hormonal levels, such as estrogen and progesterone levels, can influence the physical performance of women during the menstrual cycle. Objective: To compare the different results on physical performance during the menstrual cycle of active non-athlete women, who use or do not use contraceptives. Methods: This research constitutes a literature review article. Google Scholar was used as a database, covering the period from 2019 to 2024. Results: Different phases of the cycle, such as follicular, ovulatory and luteal, present hormonal variations that impact motivation, fatigue and physical discomfort during exercise. The luteal phase, despite increasing mood, is associated with greater discomfort, while the ovulatory phase favors performance due to the estrogen peak. Women who do not use contraceptives tend to have greater handgrip strength, indicating that contraceptives can modulate strength fluctuations. The relationship between contraceptive use and physical performance is complex, suggesting greater stability in training for users, although there are still significant variations in muscle strength and power. Conclusion: It is necessary to understand hormonal interactions to develop more effective and personalized training programs throughout the menstrual cycle.